Sensorless Solar Tracker Based on Sun Position for Maximum Energy Conversion - Syafii Ghazali; Refdinal Nazir; Kamsory , (Proceeding of the Electrical Engineering Computer Science and Informatics, 2015)
The performance of solar panels is dependent on sunlight it receives. Therefore, it is necessary to design a device that can set the direction of the solar panel always follows the sun position based solar tracker. The two-axis sensorless trackers have used in this research to produce maximum energy conversion. Position of solar panel move based on sun position using sunrise and sunset database. By using linear interpolation the sun position in latitute and longitude for other time can be obtained during a day. Based on these value the solar panel set its position using two servo motor which drived by Arduino. This technique independent from weather conditions, although cloudy, panel position remains consistent with the maximum illumination when the weather is sunny back later. By this way, the solar panel absorbs maximum sunlight and generate maximum electricity.